Acupuncture to Reduce HIV-Associated Inflammation. (2nd April 2015) - Swanson, Barbara; Keithley, Joyce K.; Johnson, Angela; Fogg, Louis; Adeyemi, Oluwatoyin; Sha, Beverly E.; Snell, Kimberly A.
Abstract : Background . HIV infection is associated with systemic inflammation that can increase risk for cardiovascular events. Acupuncture has been shown to have immunomodulatory effects and to improve symptoms in persons with inflammatory conditions. Objective . To test the anti-inflammatory effects of an acupuncture protocol that targets the cholinergic anti-inflammatory pathway (CAIP), a neural mechanism whose activation has been shown to reduce the release of proinflammatory cytokines, in persons with HIV-associated inflammation. Design, Setting, Participants, and Interventions . Double-blind, placebo-controlled clinical trial conducted in an outpatient clinic located in a medically underserved urban neighborhood. Twenty-five clinically-stable HIV-infected persons on antiretroviral therapy were randomized to receive once weekly CAIP-based acupuncture or sham acupuncture. Main Outcome Measures . Outcomes included plasma concentrations of high sensitivity C-reactive protein and D-dimer and fasting lipids. Results . Twenty-five participants completed the protocol (treatment groupn = 12, control groupn = 13 ). No adverse events related to the acupuncture protocol were observed. Compared to baseline values, the two groups did not significantly differ in any outcome measures at the end of the acupuncture protocol. Conclusions . CAIP-based acupuncture did not favorably modulate inflammatory or lipid parameters. Additional studies are warranted of CAIP-based protocols of different frequencies/durations.